2019
DOI: 10.1155/2019/5631620
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Newly Diagnosed Type 2 Diabetes in Chinese Older Adults: A National Prospective Cohort Study

Abstract: Aim To investigate the metabolic profiles of newly diagnosed type 2 diabetes (NEW2D) in Chinese older adults (≥65 years) and assess the proportion of patients who achieved the targeted goals of blood glucose, blood pressure, and blood lipid. Methods NEW2D study was an observational, longitudinal, prospective cohort study involving patients who were diagnosed with type 2 diabetes (T2D) within the past 6 months and had a follow-up of 12 months. Participants were divided into younger NEW2D group (aged 20-65 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…It was similar to that (25.9%) in Shaanxi Province in western China [31]. However, it was much lower than the national-wide data (36.7% [25]-47.8% [2,12,32]). The reason accounting for the discrepancy might be those data either from a tertiary / secondary hospital [12] or from epidemiological study [32], which might under-estimate a real-world worse situation.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…It was similar to that (25.9%) in Shaanxi Province in western China [31]. However, it was much lower than the national-wide data (36.7% [25]-47.8% [2,12,32]). The reason accounting for the discrepancy might be those data either from a tertiary / secondary hospital [12] or from epidemiological study [32], which might under-estimate a real-world worse situation.…”
Section: Discussionsupporting
confidence: 78%
“…The reason accounting for the discrepancy might be those data either from a tertiary / secondary hospital [12] or from epidemiological study [32], which might under-estimate a real-world worse situation. Because the former one may represent patients with better medical resources [12], and the later one included a lot of new-diagnosed diabetes patients who had relatively low HbA 1C [32].…”
Section: Discussionmentioning
confidence: 99%
“…[14] [15]. In a recent Chinese study involving 5770 elderly diabetic patients, it was found that the mean value of hemoglobin A1c at diagnosis was 7.9%, and after a year of follow-up, this figure decreased to 6.6% [14]. The Swedish national diabetes register also found a relatively low (6.6% -6.7%) level of hemoglobin…”
Section: Discussionmentioning
confidence: 99%
“…The HbA1c level of diagnosed T2DM was obtained from ADDITION-Europe usual care arm with the HbA1c level of 7.0 % [ 24 ]. For undiagnosed T2DM state, we applied the HbA1c level of 8.5 % among those diagnosed clinically with T2DM within the past 6 months [ 23 ]. For diabetic complications, the mean HbA1c level of 9.1 % was derived from a study in China [ 25 ].…”
Section: Methodsmentioning
confidence: 99%